Pharmacological regimens for eradication of Helicobacter pylori: an overview of systematic reviews and network meta-analysis. Issue 1 (December 2016) - Xin, Yiqiao; Manson, Jan; Govan, Lindsay; Harbour, Robin; Bennison, Jenny; Watson, Eleanor; Wu, Olivia
Abstract Background Approximately half of the world's population is infected with Helicobacter pylori (H.pylori), a bacterium shown to be linked with a series of gastrointestinal diseases. A growing number of systematic reviews (SRs) have been published comparing the effectiveness of different treatments for H.pylori infection but have not reached a consistent conclusion. The objective of this study is to provide an overview of SRs of pharmacological therapies for the eradication of H.pylori. Methods Major electronic databases were searched to identify relevant SRs published between 2002 and February 2016. Studies were considered eligible if they included RCTs comparing different pharmacological regimens for treating patients diagnosed as H.pylori infected and pooled the eradication rates in a meta-analysis. A modified version of the 'A Measurement Tool to Assess Systematic Reviews' (AMSTAR) was used to assess the methodological quality. A Bayesian random effects network meta-analysis (NMA) was conducted to compare the different proton pump inhibitors (PPI) within triple therapy. Results 30 SRs with pairwise meta-analysis were included. In triple therapy, the NMA ranked the esomeprazole to be the most effective PPI, followed by rabeprazole, while no difference was observed among the three old generations of PPI for the eradication of H.pylori. When comparing triple and bismuth-based therapy, the relative effectiveness appeared to be dependent on the choice of antibiotics within the triple therapy; moxifloxacin or levofloxacin-based triple therapy were both associated with greater effectiveness than bismuth-based therapy as a second-line treatment, while bismuth-based therapy achieved similar or greater eradication rate compared to clarithromycin-based therapy. Inconsistent findings were reported regarding the use of levofloxacin/moxifloxacin in the first-line treatment; this could be due to the varied resistant rate to different antibiotics across regions and populations. Critical appraisal showed a low-moderate level of overall methodological quality of included studies. Conclusions Our analysis suggests that the new generation of PPIs and use of moxifloxacin or levofloxacin within triple therapy as second-line treatment were associated with greater effectiveness. Given the varied antibiotic resistant rate across regions, the appropriateness of pooling results together in meta-analysis should be carefully considered and the recommendation of the choice of antibiotics should be localized.